(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
This article examines the issues of new Uzbekistan’s participation in international financial processes. In the main part of the article, the export and import issues, the main indicators of foreign economic activity are discussed. In addition, statistical indicators are analyzed by dividing them into latest periods.